2021
DOI: 10.33892/aph.2021.91.31-39
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the permeability and in vitro cytotoxicity of functionalized titanate nanotubes on Caco-2 cell line

Abstract: Titanate nanotubes (TNTs) are promising vectors for drug delivery due to their unique physicochemical properties such as biocompatibility, mechanical strength, and chemical resistivity. However, considering their strong hydrophilicity, pristine TNTs exert very limited permeability through the intestinal cell layer. The aim of this study was to turn the surface characteristics and thus enhance the permeability of TNTs by functionalization. TNTs were functionalized with trichloro(octyl)silane (TCOS) and magnesiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In the first attempt, the same method which was previously used for functionalization of TNTs with trichloro-octyl-silane [ 20 ] was adopted to TCA. Nevertheless, the trial was not successful, as shown in Figure 2 , as the characteristic peaks of TCA, mainly the C=O, C-O and C-Cl stretching vibration at 1751, 1262 and 679 cm −1 , respectively, are clearly absent in the spectrum of the corresponding composite, which suggests that it was removed during the washing procedure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first attempt, the same method which was previously used for functionalization of TNTs with trichloro-octyl-silane [ 20 ] was adopted to TCA. Nevertheless, the trial was not successful, as shown in Figure 2 , as the characteristic peaks of TCA, mainly the C=O, C-O and C-Cl stretching vibration at 1751, 1262 and 679 cm −1 , respectively, are clearly absent in the spectrum of the corresponding composite, which suggests that it was removed during the washing procedure.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that these safety results were not limited to the bare TNTs, but the safety was also evidenced with different types of functionalization and with different chemical structures. For example, Ranjous et al have reported the safety of silan-functionalized TNTs up to 1 mg/mL and stearate-functionalized TNTs up to 2 mg/mL on Caco-2 cell lines using MTT assay for a short exposure (120 min) [ 20 ]. Papa et al have also modified the surface of TNTs with polyethyleneimine (PEI) and then examined the toxicity with MTT assay on cardiomyocytes for 24 and 96 h. No significant toxicity was observed neither with TNTs nor with their functionalized samples in a concentration up to 10 µg/mL [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also an available option to tailor the surface chemistry by functionalizing it with different molecules or replacing Na + /H + ions on it with other ions such as Cu 2+ /Ni 2+ and Mg 2+ . This would help to control/adjust TNTs properties and provide them with secondary characteristics and new behaviors other than the original ones, which could be the key to overcome some of their problems and extend their application to further disciplines [60][61][62][63].…”
Section: Applications In the Pharmaceutical Fieldmentioning
confidence: 99%
“…However, the potential utilization of TNTs in health-related applications is supported by the promising results obtained by numerous studies which investigated their cytotoxicity using different cell lines (intact and cancerous) with different concentrations (range from 1 µg/mL to 5 mg/mL) and different times of exposure (from short treatment of 120 min to long exposure of 7 days) [7,8,10,85]. Even surface-modified TNTs with several molecules (silane, stearate, polyethyleneimine, acrylic acid-polyethylene glycol copolymer) have presented similar results which could promote the shifting of TNTs (bare and surface-modified) to the health domain [9,10,61].…”
Section: Applications In the Pharmaceutical Fieldmentioning
confidence: 99%